2015
DOI: 10.1186/s13000-015-0301-5
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde dehydrogenase 1 expression correlates with the invasion of breast cancer

Abstract: BackgroundAldehyde dehydrogenase 1 (ALDH1) is an important marker of tumor-initiating cells. We aimed to investigate ALDH1 expression in benign breast disease and human breast cancer of different histologic stages.MethodsImmunohistochemical staining of ALDH1 was applied to 21 cases with benign breast diseases, 47 ductal carcinoma in situ (DCIS) cases, 62 cases diagnosed with invasive cancer with extensive intraductal component (EIC), and 58 cases diagnosed with invasive cancer without EIC.ResultsALDH1 was expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 18 publications
1
16
2
Order By: Relevance
“…Our study confirms the previous observations that ALDH expression correlates with tumor grade, metastasis, and poor outcome [32,17]. Although, our sample size is small, these findings correlated with a previous publication stating that ALDH1 expression correlates with drug resistance as well as aggressive and metastatic phenotypes in breast cancer [13,48]. The evidence shows that BCSC (ALDH þ ) are multipotent and govern many signaling pathways responsible for aggressive growth, chemo-resistance, metastasis (EMT) and recurrence of the disease.…”
Section: Discussionsupporting
confidence: 92%
“…Our study confirms the previous observations that ALDH expression correlates with tumor grade, metastasis, and poor outcome [32,17]. Although, our sample size is small, these findings correlated with a previous publication stating that ALDH1 expression correlates with drug resistance as well as aggressive and metastatic phenotypes in breast cancer [13,48]. The evidence shows that BCSC (ALDH þ ) are multipotent and govern many signaling pathways responsible for aggressive growth, chemo-resistance, metastasis (EMT) and recurrence of the disease.…”
Section: Discussionsupporting
confidence: 92%
“…Its overexpression can increase the risk of alcohol-related cancers [23]. Moreover, ALDH1 has been associated with metastasis and poor prognosis in many human cancers, such as breast cancer [24], ovarian cancer [17], lung cancer [18], and pancreatic cancer [25]. …”
Section: Introductionmentioning
confidence: 99%
“…Recently, a growing number of studies have been investigating the clinicopathological and prognostic value of CSC marker ALDH1 in BC. Most of those studies showed that ALDH1 expression was associated with poor prognostic parameters and worse clinical outcome in BC patients [3,[7][8][9][10][11]. In this study, we immunohistochemically evaluated ALDH1 expression in a series of 217 invasive breast carcinomas and analyzed the correlation between ALDH1 expression and clinicopathological parameters, molecular subtypes of BC, and patient survival.…”
Section: Discussionmentioning
confidence: 99%
“…Pan et al [8] showed a lower rate of ALDH1 expression in cases with DC in situ (DCIS) and a higher in patients with invasive cancer without extensive intraductal component (EIC). Notably, in the same tumor, the rate of ALDH1 expression was higher in the invasive component than in the in situ component.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation